Arterial stiffness and its association with dyslipidemia - Mohd Rus, Razman; Ab Rahman, Jamalludin; Muhammed Nordin, Ellyda; Akter, Seikh Farid Uddin (Faculty of Medicine, International Islamic University Malaysia, 2013)
Background: Cardiovascular diseases (CVD) are the leading cause of mortality in Malaysia as well as in other countries. It is associated with, inter alia, many risk factors, such as increasing age, hypertension, diabetes, dyslipidemia, oxidative stress and autonomic dysfunction and arterial stiffness. Objective: The focussed objectives of this study were to measure the prevalence of arterial stiffness and to assess its association with dyslipidemia. Methodology: A cross sectional study was conducted in a rural community in Malaysia. Data were collected using an interviewer administered questionnaire which included three sections – sociodemographic characteristics, personal profile, and past medical history. In addition, Seca Body Meter (Seca 220) was used to measure height and weight. Sphygmomanometer (OMRON Automatic Blood Pressure Monitor HEM 907) and SphygmoCor-AtCor MM3 SERIAL/RS-232 were used for blood pressure and augmentation index (AIx) measurement. Data were analysed using the SPSS for Windows, Version 18.0. Results: The mean age of respondents was 49.5 years, SD±15.6. The prevalence of arterial stiffness was 23.3% (95% Confidence Interval (CI): 16.44 – 30.16). The prevalence of dyslipidemia was 82.9% (95% CI: 76.79 – 89.01). Multivariate logistic regression revealed that total cholesterol was significantly associated with arterial stiffness (OR=4.56, CI 1.10-18.90). Conclusion: The prevalence of dyslipidemia was high. Despite an insignificant association between dyslipidemia and AIx, there is a significant association between TC level and Aix.